1992
DOI: 10.1007/bf00246872
|View full text |Cite
|
Sign up to set email alerts
|

Synovial, articular cartilage and bone changes in rapidly destructive arthropathy (osteoarthritis) of the hip

Abstract: We studied ten femoral heads from eight patients suffering from rapidly destructive arthropathy (RDA) of the hip. At surgery, 1-3.5 ml of synovial fluid, ranging from citrous to hemorrhagic, was aspirated from six joints. This fluid was viscous, pauci-cellular and did not contain calcium pyrophosphate dihydrate (CaPPD) crystals, although significant amounts of alizarin S-positive material was found in three joints. Significant synovial hyperplasia was found in four joints and moderate hyperplasia in two. Synov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…MMP-9 can also be produced by activated osteoclasts (34). A number of osteoclasts in rapidly destructive hip OA, which are one source of MMP-9, have been observed around necrotic bone in subchondral areas (23,24). A recent study also demonstrated that MMP-9 was strongly expressed in the subchondral region in RA patients (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-9 can also be produced by activated osteoclasts (34). A number of osteoclasts in rapidly destructive hip OA, which are one source of MMP-9, have been observed around necrotic bone in subchondral areas (23,24). A recent study also demonstrated that MMP-9 was strongly expressed in the subchondral region in RA patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMP-3 could be released from chondrocytes into the synovial fluid by rapid degeneration of articular cartilage. In rapidly destructive hip OA, articular cartilage is extensively lost, and subchondral bone is invaded by synovial and fibrous connective tissue (24,25). Thus, large amounts of MMP-3 produced and released as described above could be drained into the bloodstream directly by the subchondral intramedullary microcirculation, or it could be drained from the synovial fluid via the blood-synovium barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In the joint fluid, a high level of tartrate-resistant acid phosphatase 5b (4190 mU/ dl) was confirmed, indicating high bone resorption within the hip joint [6]. These findings are characteristic of RDA [6][7][8].…”
Section: Introductionmentioning
confidence: 70%
“…Some authors reported significantly greater counts of osteoclasts in active areas of rapid destructive arthritis as compared to ordinary hip arthritis, in addition to vascular-rich granulation, indicating that vascularity may be an important factor in the process of lysis and destruction of bone [14][15][16]. Recent reports have shown the existence of subchondral insufficiency fracture in rapid destructive arthritis of the hip joint [14][15][16][17][18][19].…”
Section: Pathophysiologymentioning
confidence: 97%
“…Recent reports have shown the existence of subchondral insufficiency fracture in rapid destructive arthritis of the hip joint [14][15][16][17][18][19]. Subchondral bone ischemia and cell necrosis have been considered major factors in the development of rapid destructive arthritis of the hip [14,15]. Some researchers supported the hypothesis that an insufficiency fracture of the femoral head precedes the occurrence of the disease [16][17][18].…”
Section: Pathophysiologymentioning
confidence: 98%